The Microbiome and Epigenetic Regulation in Bone Metabolism: Implications for Osteoporosis - Celoch, Kornel; Porczyński, Andrzej; Cegielski, Jakub; Kruk, Kamil; Bulanda, Jakub; Bukowczan, Elżbieta; Ślęzak, Jakub; Wojciech, Daniel; Jabrzyk, Martyna (Journal of Education, Health and Sport, 2025)
Introduction: Osteoporosis is a common metabolic disorder associated with aging, characterized by a progressive loss of bone mass and microarchitectural deterioration, leading to an increased risk of fractures and diminished quality of life. Emerging evidence has identified the gut microbiota as a novel regulator of bone homeostasis, implicating intestinal microbial populations in the etiology of osteoporosis and bone metabolism. Understanding the pathways through which the gut microbiome influences skeletal integrity is crucial for advancing targeted strategies in the prevention and management of osteoporosis. Aim of Study: This study aims to summarize current knowledge regarding the role of the gut microbiome in the regulation of bone metabolism and its impact on the development and progression of osteoporosis. The review explores the mechanisms through which microbiota influence skeletal homeostasis, evaluates their contribution to osteoporosis susceptibility, and examines the consequences of microbiome changes on bone integrity. Materials and Methods: A literature search across PubMed using keywords: “osteoporosis,” “bone metabolism,” “gut microbiome,” “microRNAs,” “epigenetics,” and “bone remodeling.” Conclusion: Osteoporosis is increasingly understood as a condition influenced not only by hormonal and nutritional factors but also by the gut microbiota and epigenetic regulators such as microRNAs. These components modulate bone remodeling by affecting osteoblast and osteoclast activity through metabolic and immune pathways. The gut-bone axis and microbiota-miRNA interactions represent a dynamic regulatory network contributing to bone health. Dysbiosis and miRNA dysregulation may disrupt this balance, increasing susceptibility to osteoporosis. Recognizing these mechanisms broadens the understanding of osteoporosis and highlights new opportunities for biomarker discovery and microbiome- or miRNA-targeted therapies.